KHASIAT WORTEL TERHADAP TEKANAN DARAH PADA PENDERITA HIPERTENSI (STUDI KASUS DI DESA BULUSULUR, WONOGIRI) - Nita Yunianti Ratnasari; Alviatianshi Meilasari (Akademi Keperawatan Giri Satria Husada Wonogiri, 2021)
Background: Hypertension is a disease of high blood pressure which when measured with a sphygmomanometer the results exceed the normal value, which is more than 120/80 mmHg (millimeters of mercury). Hypertension can also be called the